Strategi Komunikasi Pemasaran Desa Adat Pecatu Dalam Mengelola Objek Wisata Uluwatu - Noviandani, Ni Kadek Wiwien; Purnawan, Ni Luh Ramaswati; Pradipta, Ade Devia (E-Jurnal Medium; Vol 2 No 2 (2021): Jurnal Ilmu Komunikasi Vol 2 No 2 Tahun 2021, 2022)
Uluwatu is a temple on a cliff in Bali. This study aimed to determine the integrated marketing communication strategy used by the Uluwatu tourist attraction manager to increase tourist visits. The researcher uses qualitative research methods to find out the marketing communication strategy for Uluwatu tourism objects and how the management of Pecatu Village regarding Uluwatu tourism objects.The data obtained described under the reality in the field then presented in the form of sentences.The data was obtained through an in-depth and literature study. The results showed that the strategy used by the Pecatu Traditional Village in managing Uluwatu tourism objects was through social media marketing celebrity endorsements, and print media, namely brochures. During the communication process between the Uluwatu tourist attraction managers and tourists,only two media have given positive responses:Instagram-where tourists always upload photos and videos about their visits made at Uluwatu attractions;Google business to provide experiences during their visit.